DISPOSISI MATEMATIS DAN PEMBELAJARAN MATEMATIKA HUMANIS BAGI MAHASISWA PENDIDIKAN MATEMATIKA - Jamiah, Yulis (Jurnal Pendidikan Matematika dan IPA, 2018)
ABSTRAKThis research purposed to obtain the overview of mathematical disposition of student mathematics education, especially the students who took number theory subject. In obtaining these overview will be applied by humanis mathematics learning model. The specific purpose of this research are: 1) describe mathematics disposition of the students; 2) describe the process of application model to increase mathematic dispositions of the student; 3) describe the effectiveness of application model. The purposes are achieved through several stages, including: 1) analyze the theoretical; 2) explore the characteristics of a mathematical disposition; (3) identify and analyze problems; (4) reviewing the learning model; (5) applying model to increase mathematic dispositions that based on observation; 6) gives a questionnaire about mathematical disposition; and 7) analyzing the data. The method used in this research is descriptive method. Based on the purpose that disclosed, the results of research: 1) mathematical disposition of the students after the application model, shows 74% very positive attitude; 24% positive attitude; and 2% doubtful attitude; 2) the process of application model that facilitates appearance of a mathematical disposition of the students based on ability cognitive domain, affective domain, and domain skills, showing the criteria very well and good; and 3) the application of humanis mathematics learning model effective to increase mathematics disposition of the students in Number theory subject. Keywords: Humanis Mathematics Learning Model, Mathematical Dispositions